Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/8433997
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Gastrointestinal Parasites of Dromedary Camels in Administrative Zone Three of Afar Region, Ethiopia

Abstract: Gastrointestinal parasites are the major threats to camel production and productivity losses in pastoral communities of Ethiopia. A cross-sectional study was conducted starting from September 2017 to April 2018 in Administrative Zone three of the Afar Region, Ethiopia. The objectives of the study were to determine the prevalence and associated risk factors for gastrointestinal parasites in camels. Fecal samples were collected aseptically from the rectum, and floatation and sedimentation techniques were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…The overall prevalence of gastrointestinal parasitic infection reached 80% among dromedary camels in Giza Governorate, Egypt. This result might be in accordance with those obtained by Mahmuda et al (2014) in Nigeria (78%); Hamed (2018) in Assiut Governorate Egypt (77.5%); Bekele et al (2022) in Ethiopia (76%); Djerbouh et al (2018) in Ethiopia (73.8%); El-Khabaz et al (2019) in Egypt (60%). Meanwhile, relatively low incidence of infection was recorded by Ahmed et al (2013) Qaluobia Governorate in Egypt (51.02%); Bouasla et al (2023) in Algeria (32.6%) and et al ( 2013) in Pakistan (37.33%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall prevalence of gastrointestinal parasitic infection reached 80% among dromedary camels in Giza Governorate, Egypt. This result might be in accordance with those obtained by Mahmuda et al (2014) in Nigeria (78%); Hamed (2018) in Assiut Governorate Egypt (77.5%); Bekele et al (2022) in Ethiopia (76%); Djerbouh et al (2018) in Ethiopia (73.8%); El-Khabaz et al (2019) in Egypt (60%). Meanwhile, relatively low incidence of infection was recorded by Ahmed et al (2013) Qaluobia Governorate in Egypt (51.02%); Bouasla et al (2023) in Algeria (32.6%) and et al ( 2013) in Pakistan (37.33%).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the age, in the current study older camels had the highest prevalence of strongyles group 54.5% (p< 0.05). That might go parallel with previous reports (Ahmed et al 2020;Hasan et al 2021;Bekele et al 2022) who declared that older camels were more likely to possess GIPs. It might be due to that by increasing the age of camels, there would be more exposure to the infection.…”
Section: Discussionsupporting
confidence: 90%
“…The present findings of Trichostrongylus sp., Haemonchus sp., Oesophagostomum sp., Trichuris sp., and E. cameli confirm this trend. Previous studies showed that camels were often co-infected with a large number of parasite species [7,9,24,25], reaching up to 14 different species in a single animal [4]. Having in mind favorable conditions for parasites spreading in zoos, the occurrence of this multiple infection in the present case is not a surprise.…”
Section: Discussionmentioning
confidence: 51%